Exploring junior high school students' geometry self-efficacy in solving 3D geometry problems through 5E instructional model intervention: A grounded theory study - Sudirman, Sudirman; García-García, Javier; Rodríguez-Nieto, Camilo Andrés; Son, Aloisius Loka (Jurnal Infinity, 2024)
Geometry self-efficacy is an essential affective aspect that will influence students in solving mathematics problems, especially geometry material. Therefore, teachers must be able to develop learning instructions that not only affect students' mathematical abilities but also strengthen students' affective aspects. This research explores students' geometry self-efficacy when learning to solve three-dimensional geometry problems through the 5E Instructional Model intervention. A grounded theory design was used to reveal the aims of this research. Participants in this research were one mathematics teacher and 22 students (12 girls and 10 boys) in class VIII at a state Junior High School in Indramayu Regency, Indonesia. The research involved the qualitative analysis of gathered data obtained through observation, questionnaires, interviews, and documentation, employing grounded theory analysis techniques, including open coding, axial coding, and selective coding. The findings revealed that students with high self-efficacy in geometry display confidence in describing and calculating the surface area and volume of three-dimensional geometric objects. Those with moderate self-efficacy in geometry are self-assured in addressing straightforward assignments but may need more confidence in tackling more complex tasks. Conversely, students with low self-efficacy in geometry tend to need more confidence and are prone to giving up easily. Therefore, this research emphasizes that the geometry self-efficacy level can influence how students act and complete 3D geometry tasks given by teachers in learning, especially 3D geometry learning.